2014
DOI: 10.1371/journal.pone.0104746
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 Induces Connective Tissue Growth Factor Expression in Human Lung Fibroblasts through the Rac1/ERK, JNK, and AP-1 Pathways

Abstract: CXCL12 (stromal cell-derived factor-1, SDF-1) is a potent chemokine for homing of CXCR4+ fibrocytes to injury sites of lung tissue, which contributes to pulmonary fibrosis. Overexpression of connective tissue growth factor (CTGF) plays a critical role in pulmonary fibrosis. In this study, we investigated the roles of Rac1, extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and activator protein-1 (AP-1) in CXCL12-induced CTGF expression in human lung fibroblasts. CXCL12 caused concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 64 publications
3
72
0
Order By: Relevance
“…Another chemokine, CXCL12, also known as stromal cellderived factor (SDF-1), attracts fibrocytes to injured lungs and induces CTGF expression in pulmonary fibroblasts, which are both dependent on its cell-surface receptor CXCR4, thus contributing to lung fibrosis [190,191]. A more detailed overview of the roles of chemokines in fibrosis can be found elsewhere [189,190].…”
Section: Ccl2 Cxcl12 and Other Profibrotic Chemokinesmentioning
confidence: 99%
“…Another chemokine, CXCL12, also known as stromal cellderived factor (SDF-1), attracts fibrocytes to injured lungs and induces CTGF expression in pulmonary fibroblasts, which are both dependent on its cell-surface receptor CXCR4, thus contributing to lung fibrosis [190,191]. A more detailed overview of the roles of chemokines in fibrosis can be found elsewhere [189,190].…”
Section: Ccl2 Cxcl12 and Other Profibrotic Chemokinesmentioning
confidence: 99%
“…It is known that Rac1 signaling regulates CTGF expression [16,23]. Lin et al [16] showed that CXCL-12 activates Rac1 signaling which induces the expression of CTGF in human lung fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [16] showed that CXCL-12 activates Rac1 signaling which induces the expression of CTGF in human lung fibroblasts. CTGF is the downstream mediator of TGFβ-induced adventitial remodeling in carotid angioplasty [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The downstream intracellular signaling transduction pathways including Phosphatidylinositol 3-kinase (PI3K)/Akt/ mammalian target of rapamycin (mTOR), Rac1/extracellular signal-regulated kinase (ERK), mitogen-activated protein kinase (MAPK), p38MAPK, stress-activated protein kinase (SAPK), c-Jun N-terminal kinase (JNK)/ activator protein-1 (AP-1), Janus kinase/signal transducers and activators of transcription (JAK/STAT). 45,46 CXCR4 is the predominant chemokine receptor on human fibrocytes. More and more evidence have indicated that substantial numbers of CXCR4 + fibrocytes can migrate and accumulate in lung in response to CXCL12 during pulmonary fibrosis.…”
Section: Cxcl12/cxcr4 Axis Mediated Fibrocyte Trafficing In Pulmonarymentioning
confidence: 99%